O34 Item response theory modeling; old kid on the block to improve pediatric drug dosing. Issue 6 (17th May 2019) - Krekels, EHJ; Välitalo, PAJ; Goulooze, SC; de Kluis, T; van Dijk, M; Simons, SHP; Tibboel, D; Knibbe, CAJ
Abstract : Background: Quantification of changes in disease states or clinical conditions is essential to establish drug effects and dosing guidelines. When single endpoints for direct measurements are lacking, multi-factorial observational scales may be used, like for instance pain or sedation scales. 1 2 Methods: Analysis of data from multi-factorial observational scales is commonly based on total scores. This assumes each item to be equally informative, which is generally not true. Item Response Theory (IRT), a long existing method in social sciences and psychology, has only recently been recognized for its ideal applicability to the analysis of multi-factorial observational scales. In this approach a latent variable is derived from all item-level data and the information that each item adds to establishing the latent variable is being weighted appropriately. The basic concepts, assumptions and applications of IRT in pharmacological research are introduced and illustrated with examples from studies on analgesia and sedation in the PICU and NICU. Results: With IRT modeling, the performance of individual items of the COMFORT and PIPP scales were assessed, and the information or noise that each item adds to the total score was quantified. 3 By introducing IRT in a population pharmacokinetic-pharmacodynamic modelling approach, the effect of morphine was establish on both procedural pain in preterm neonates 4 and post-operative pain at rest in children [unpublished data]. For this, statistical significance of drug effects were evaluated based on changes in the latent variable and back calculation to the total score of the observational scales allowed for the clinical interpretation of findings. Conclusion: IRT offers a desperately needed data analysis framework that may revolutionize pharmacological studies for diseases or conditions that cannot be directly quantified in children. New techniques augmenting the performance of the classical IRT approach when assumptions are violated are currently being developed in our group. References: van Dijk M, de Boer JB, Koot HM Tibboel D, Passchier J, Duivenvoorden HJ. The reliability and validity of the comfort scale as a postoperative pain instrument in 0 to 3-year-old infants. Pain 2000 Feb;84(2–3):367–77. Stevens B, Johnston C, Petryshen P, Taddio A. Premature infant pain profile: development and initial validation. Clin J Pain . 1996 Mar;12(1):13–22. Välitalo PA, van Dijk M, Krekels EH, Gibbins S, Simons SH, Tibboel D, Knibbe CA. Pain and distress caused by endotracheal suctioning in neonates is better quantified by behavioural than physiological items: a comparison based on item response theory modelling. Pain . 2016 Aug;157(8):1611–7. Välitalo PA, Krekels EH, van Dijk M, Simons S, Tibboel D, Knibbe CA. Morphine pharmacodynamics in mechanically ventilated preterm neonates undergoing endotracheal suctioning. CPT Pharmacometrics Syst Pharmacol . 2017 Apr;6(4):239–248 Disclosure(s): Nothing to disclose